Defining Future Strategies of Warehouse Receipt System Corporation With BCG Matrix Analysis (Case PT Food Station Tjipinang Jaya, Geneng Village, Geneng Sub-District, Ngawi Regency) - Andromeda Andromeda; Syarif Imam Hidayat; Mubarokah Mubarokah (PT. Publikasiku Academic Solution, 2023)
The purpose of this research is to formulate the future strategies for warehouse receipt system corporation (PT Food Station Tjipinang Jaya) in Geneng Village, Geneng Sub-District, Ngawi Regency. This research uses Boston Consulting Group matrix analysis and use secondary data from BAPPEBTI as warehouse receipt system (WRS) regulator. Using data from BAPPEBTI (2020-2021) that consist of 7 rice commodity WRS managers, then reduced to 4 rice commodity WRS managers including PT Food Station Tjipinang Jaya. The management of PT Food Station Tjipinang Jaya Strategy decide to conduct strategic formulation using BCG matrix analysis between PT. Tjipinang Jaya Food Station and also 3 of its competitors during 2020-2021 for the rice commodity WRS business. And the results of this analysis it is known that PT Food Station Tjipinang Jaya has a market share of 47.20% and a market growth of 51.59%. Meanwhile, the relative market share value of PT Food Station Tjipinang Jaya is 0.513 times. PT. Tjipinang Jaya Food Station is in quadrant II (0.513 : 51.59%), namely the STARS quadrant. In this quadrant shows the performance of PT. Food Station Tjipinang Jaya with high market growth and relatively high market share. In the STARS quadrant, the strategy adopted by PT. Tjipinang Jaya Food Station is a strategy related to improving warehouse receipt system services consist of : integration strategies (backward, forward and horizontal), market penetration strategy, market development strategy and product development strategy.